Thinking Media Aesthetics Media Studies, Film Studies and the Arts - Hausken, Liv (Peter Lang International Academic Publishing Group, 2013)
Thinking Media Aesthetics investigates the field between media studies and the aesthetic disciplines. It presents an interdisciplinary program for aesthetic analysis and theoretical reflection. It stages a conversation around basic concepts in the field, like «medium» and «media», and about how we might best go about studying these terms.